(untitled) - García Rodríguez, Alba (Romanica Olomucensia, 2012)
Present tense is the most widely used tense in the Spanish verbal system. Although this tense normally appears related to present situations, it can show a big variety of meanings depending on the context. In this paper, we analyze the main uses of the present tense in the Colombian soap opera called Sin tetas no hay paraíso, based on the novel written by Gustavo Bolívar. This is a good material to study because of its dynamic and realistic dialogues, so we can know the Spanish spoken in Colombia nowadays. We analyze the different uses of the present tense and the relations with the rest of the elements of the statement (horizontal relationships). It is discovered that there is a great variety of uses and meanings of the present tense also in this Colombian soap opera.
Keywords: present tense; soap opera; Colombian Spanish; spoken Spanish; descriptive analysis.